Bioconvection in Porous Square Cavity Containing Oxytactic Microorganisms in the Presence of Viscous Dissipation - Alluguvelli, Ramesh; Balla, Chandra Shekar; Naikoti, Kishan (Discontinuity, Nonlinearity, and Complexity, 2026)
This is paper reports an investigation of oxytacic-bioconvective flow in a porous square cavity under the influence of viscous dissipation. Darcy model of Boussinesq approximation is employed to formulate the bioconvective flow in the porous medium. The governing nonlinear partial differential equations are nondimensionalised using suitable dimensionless parameters then solved by Galerkin finite element method. The computational numerical results are described by the surface plots of stream function, temperature, concentrations of oxygen and microorganisms, average Nusselt number, average Sherwood numbers of concentrations of oxygen and microorganisms. The effects of key parameters such as Peclet number (Pe), Rayleigh number of bioconvection (Rb), Eckert number (Ec), Lewis number (Le) and Rayleigh number (Ra) are presented and inspected. Eckert number (Ec) and Peclet number (Pe) improve the bioconvection flow and rate of heat transfer. It is also observed that the isoconcentration patterns of oxygen and microorganism density are controlled by Ec and Pe.